Co-creative service design for online businesses in post-COVID-19 - Shamim, A. (Emerald Group Holdings Ltd., 2021)
Purpose: This study aims to explore the customersâ behaviour towards online shopping during COVID-19 in a Muslim country and proposes a co-creative service design for online businesses (webstore) in the post-COVID-19 era. Design/methodology/approach: The study used a qualitative design for collecting the data where in-depth interviews from 18 customers were conducted following the qualitative design protocol. Due to the limitation of physical distancing, the interviews were conducted online using Microsoft teams. Findings: Based on the findings, new potential services are proposed for webstores for customer engagement, the need for expansion of product lines and safety measures for customers and staff during and post-COVID-19 era. Following the findings, a co-creative service design is proposed for webstores to revamp the business during and post-COVID-19. Originality/value: The study is unique because it has developed various unique strategic factors essential for revamping online businesses for better growth in post-COVID-19. The proposed new co-creative service design model for an online service provider is expected to create customers engagement and loyalty during and in post-COVID-19. Â© 2021, Emerald Publishing Limited.